Land Tenure Among Non-Hispanized Filipinos - Zialcita, Fernando N (Archīum Ateneo, 2000)
Generally held is that communal ownership of land was the norm before Spaniards introduced individual land ownership. There are problems with this supposition. Overlooked is that land tenure is influenced by the means of production. Where shifting cultivtion was the norm both in the uplands of the early 20th century and the 16th century, private, individual ownership of land was not regarded as relevant. However, where permanent, wet rice cultivation was normative, land was owned privately.